Enhanced community support reduces rhino poaching in Nepal - Esmond Martin; Chryssee Martin (Pachyderm)
Rhino poaching in Nepal declined in 2008 and 2009 in contrast to the previous seven years. Among the primary reasons for this decrease were the improved law and order throughout the country and better anti-poaching efforts. NGOs allocated more resources to local communities living around Bardia and Chitwan National Parks, and an increase in tourism meant that the Parks’ Buffer Zone Management Committees received more money and assistance from the Department of National Parks and Wildlife Conservation (DNPWC). Lower caste people who understand the needs of the poorest were elected to senior positions on the Management Committees and User Groups in the Buffer Zones. In turn, these developments encouraged the mostly poor people of the local communities to support more fully rhino protection. Improved co-operation amongst the NGOs, DNPWC, the Army and local communities helped reduce rhino poaching in 2008 and 2009.